2012
DOI: 10.1111/j.1442-2018.2012.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety and falls: A qualitative study of home care nurses in Norway

Abstract: This study explored patient safety and falls, based on the experiences of home care nurses. Four focus group interviews were conducted with 20 home care nurses. The data were analyzed by content analysis. This study identified the following four themes: (i) patient safety was not viewed as primary prevention; (ii) the lack of investigation into causes of falls; (iii) the frailty of older people who can no longer live at home independently and safely; and (iv) patient autonomy versus patient safety. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
1
20
0
2
Order By: Relevance
“…The qualitative phase of the study also emphasizes that the preventive approach in the elderly is addressed exclusively by the nursing staff. In both contexts, some health professionals did not perceive the fall risk approach as a primary and priority prevention, focusing exclusively on the treatment of the consequences of falls 22 . In this sense, the nursing records related to the diagnosis and interventions were very scarce, evidencing a lack of awareness of the fall 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative phase of the study also emphasizes that the preventive approach in the elderly is addressed exclusively by the nursing staff. In both contexts, some health professionals did not perceive the fall risk approach as a primary and priority prevention, focusing exclusively on the treatment of the consequences of falls 22 . In this sense, the nursing records related to the diagnosis and interventions were very scarce, evidencing a lack of awareness of the fall 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Portanto, é um efeito acumulativo das alterações relacionadas à idade, doenças, meioambiente e pessoal inadequado que predispõem o indivíduo às quedas (13,14) . (17) .…”
Section: Fatores Relacionados à Ocorrência De Quedasunclassified
“…However, Berland et al . () found that clinicians are more concerned with fall treatment than fall prevention because they tend to place their patients' autonomy before these patients' safety. Spanaki et al .…”
Section: Introductionmentioning
confidence: 99%
“…staff and patient safety education, fall-risk assessments, patient fall-risk alerts, environmental and equipment modifications, medication management and assistance with transfer and toileting) (Spoelstra et al 2012). However, Berland et al (2012) found that clinicians are more concerned with fall treatment than fall prevention because they tend to place their patients' autonomy before these patients' safety. Spanaki et al (2012) found that the prevalence of falls could not be significantly reduced after implementing stricter safety procedures (e.g.…”
Section: Introductionmentioning
confidence: 99%